Pernikahan Dini dan Implikasinya Pada Angka Putus Sekolah di Desa Tumbang Habaon Kecamatan Tewah Kabupaten Gunung Mas - Lina Sari; Eli Karliani; Dotrimensi, Dotrimensi (FKIP, Universitas Palangka Raya, 2023)
This research aims to describe early marriage and its implications for school dropout rates in Tumbang Habaon Village. This research is qualitative research with a descriptive approach. The results of this research are (1). Description of early marriage. The implications for the school dropout rate in Tumbang Habaon village, Tewah sub-district, Gunung Mas Regency. This has happened, with several school-age children having early marriages while still at school. Early marriage often occurs in this village, which is caused by the majority of people marrying at a young age. This has a major impact on public education, resulting in generally low levels of education. In addition, in this village, educational services only cover junior secondary education, whereas to continue to senior secondary level, children have to leave the village. This causes children to go to school without parental supervision. (2) The main factor that causes early marriage to occur is the child's desire to get married and it is supported by the blessing of the parents so that the marriage will happen. This is also supported by the rule that there are no sanctions for early marriage so that people are very free to get married. at an early age. Apart from that, there are economic, social and cultural factors that occur in the community